Answer:
The Answer is B
Step-by-step explanation:
The equation of a circle in standard form is
(x - h)² + (y - k)² = r²
where (h, k) are the coordinates of the centre and r is the radius
Here diameter = 12, thus radius = 12 ÷ 2 = 6 and (h, k) = (2.5, - 3.5), thus
(x - 2.5)² + (y - (- 3.5))² = 6², that is
(x - 2.5)² + (y + 3.5)² = 36 ← equation of circle
Answer: The graph shows exponential decay
The graph shows y = 2^x reflected over the y-axis
Step-by-step explanation:
When<u> 0<b<1 </u>, the graph shows <u>exponential decay</u>. In this case, b was equal to 1/2 as shown by the graph alongside the question. Therefore, the graph shows exponential decay.
The graph of y = 2^x would show a reflection of y = 1/2 ^x over the y-axis, therefore the graph shows <u>y = 2^x reflected over the y-axis</u>.
57.8% is greater than 57.68%
36 squared + 12 squared = AD squared
1296 + 144 = AD squared
square root of 1440 = AD
37.95
Answer:
17
Step-by-step explanation:
12 -6 divided by 3 is 2, so 15+2 is 17